Digital consumers reshaping the information professions - Nicholas, David 1947-; Rowlands, Ian (Facet, 2008)
The information professions - librarianship, archives, publishing and, to some extent, journalism - have been rocked by the digital transition that has led to disintermediation, easy access and massive information choice. Professional skills are increasingly being performed without the necessary context, rationale and understanding. Information now forms a consumer commodity with many diverse information producers engaged in the market. It is generally the lack of recognition of this fact amongst the information professions that explains the difficulties they find themselves in. There is a need for a new belief system that will help information professionals survive and engage in a ubiquitous information environment, where they are no longer the dominant players, nor, indeed, the suppliers of first choice. The aim of this thought-provoking book is to provide that overarching vision, built on hard evidence rather than on PowerPoint 'puff'. An international, cross-sectoral team of contributors has been assembled for this purpose. Key strategic areas covered in this book include: the digital consumer - an introduction and philosophy; the digital information marketplace and its economics - the end of exclusivity; the e-shopper - the growth of the informed purchaser; the library in the digital age; the psychology of the digital information consumer; the information-seeking behaviour of the digital consumer - case study - the virtual scholar; the Google generation - myths and realities about young people's digital information behaviour; and, trends in digital information consumption and the future. Where do we go from here? No information professional or student can afford not to read this far-reaching and important book